Effect of antihistamine as an adjuvant treatment of isotretinoin in acne: a randomized, controlled comparative study. (21st February 2014) - Lee, H.E.; Chang, I.K.; Lee, Y.; Kim, C.D.; Seo, Y.J.; Lee, J.H.; Im, M.
Abstract Background Isotretinoin has been frequently used for acne therapy. However, it has limitation in acceptance because of its adverse effects. Although antihistamine recently revealed to decrease the lipogenesis, evidence is lacking regarding the clinical relevance of antihistamine in the treatment of acne. Objectives To evaluate the clinical efficacy and tolerability of antihistamine as an adjuvant treatment of isotretinoin. Methods Forty patients with moderate acne were included in this randomized, controlled comparative study. Twenty patients were treated with isotretinoin and 20 patients were treated with additional antihistamine, desloratadine. Assessment was made at baseline, after 2, 4, 8 and 12 weeks of treatment. Results At week 12, compared with isotretinoin only group, isotretinoin with additional antihistamine group showed more statistically significant decrease in acne lesion counts (non‐inflammatory lesions: 44.8% vs. 17.8%; inflammatory lesions: 55.8% vs. 22.9%; total lesions: 45.6% vs. 18.7%; all P < 0.05). Significant decrease was also observed in the score of global acne grading system and the measured value of sebum and erythema. Moreover, acne flare during the treatment occurred less frequently and adverse events of isotretinoin were more tolerable in additional antihistamine group. Conclusions This results provide early evidence that antihistamine has a synergic effect with minimizing the side‐effect of isotretinoin, and may be used as an adjuvant treatment of moderate acne.